Analisis Manajemen Risiko Operasional pada Bank Sumsel Babel Syari’ah KC. Belitang - Imam Royani Hamzah; Rista Amelia; Siti Khusnia (Jurnal Pendidikan Indonesia, 2025)
This study aims to analyze the operational risk management control system at Bank Sumsel Babel Syariah KC Belitang. Risk control in banking is very necessary in order to maintain customer trust. Operational risk occurs when there is a failure or malfunction of internal processes, human error, and system failures, or due to external events. The operational risks studied in this study are information and technology (IT) systems, human error and operational risk management systems at Bank Sumatra Babel Syariah KC Belitang. This research uses a qualitative descriptive method. Data collection techniques through interviews and documentation on related parties. The results of this study show that the operational management process that occurs at Bank Sumsel Babel Syariah KC Belitang has shown a good commitment in the process of implementation, management, and control, especially handling human error, but is still weak in the management and control of IT systems.